AN ANALYSIS ON THE PLOT OF JANE AUSTENS NOVEL “PRIDE AND PREJUDICE” - Arbain Arbain (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2016)
This study reports an analysis of the plot used in the novel written by Jane Austens, Pride and Prejudice.  Using qualitative approach that focused on content analysis, this study presents three kinds of findings. Respectively, the findings are: (1) conflict on which the plot turns, (2) chief episodes or incidents that make up the plot, and (3) plot in terms of its exposition, complication, crisis/climax, falling action and denouement.  Conflicts in the novel are nicely to read and the development of the conflicts is smooth.  Resolution is given in a direct way.  Chief episodes that built up the conflict consist of 15 events from which the ending of the conflicts are easily to guess but nicely to follow.  Finally, plots that make up the story concise, smooth, and interesting are supported using simple dialogues, conversations, and plausible resolution.